A infância em processos judiciais em Belém do Pará: da criminalidade aos discursos jurídico-assistencialistas para a educação do menor desvalido (1890-1930) - CORRÊA, Liliane da Silva França (Universidade Federal do Pará, 2019)
The present study aims to analyze childhood in legal proceedings in Belém do Pará, based on the problem of crime, from the perspective of legal-assistentialist discourses for the education of underprivileged children from 1890 to 1930. Cases of minors: Joaquim Manoel da Silva, 13 years old, and Manoel dos Santos, 16 years of age, accused of various crimes. The judicial process is inserted in the context of the socioeconomic transformations of Belém in the passage from the nineteenth century to the twentieth century, which contributed to the increase of crime in the capital of Pará, due not only to the commercialization of rubber, but also to the project to modernize the city of Belém and of a new educational proposal of justice for poor children involved with crime in Brazil. However, this proposal was fostered in a work oriented education model, whose initiatives were based on the understanding of the alliance between Justice and Assistance, inserted in the philanthropic model logic, aiming at the moral sanitation of the society to focus on the poor, abandoned child ; and in the first code of Minors "Mello Mattos", implemented in 1927, thus enabling the system of assistance and protection for underprivileged minors. Thus, the questions that guide this study are: What discourses are present in the judicial processes of minors, Joaquim Manoel da Silva and Manoel dos Santos, on crime in Belém do Pará from 1890 to 1930? In view of this central question, we propose to raise some specific questions: What senses and meaning in the discursive statements are present in the judicial processes of minors, Joaquim Manoel da Silva and Manoel dos Santos? What ideological formation is contained in the discursive statements of the victims, witnesses and curators in the judicial processes on child crime in the capital of Pará? What is the educational proposal for the underprivileged minor in Republican Brazil from the legal-assistance discourses? In order to try to answer such questions, from the main objective of this study, I intend to: 1 - identify the meanings and meanings in the discursive statements present in the judicial processes of minors, Joaquim Manoel da Silva and Manoel dos Santos; 2 - to point out the ideological formation contained in the discursive statements of the victims, witnesses and curators in the judicial processes on child crime in the capital of Pará and; 3 - analyze the educational proposal for the underprivileged minor in Republican Brazil from the legal-assistentialist discourses. Child crime was directly linked to poverty, abandonment of the family, the demographic explosion and the modernization project of the city of Belém, which looked at the social, economic and political convergences and divergences that occurred in several capitals of the country, contributing to the emergence of less criminal. Against the Pará elite, which emerged in the Belle Époque, there was a population of poor children assigned to commit vagrancy, vagrancy, and theft crimes. The corpus of this research encompasses two judicial proceedings, collected in the archive of the Memory Center of Amazonia and belonging to the documentation of the Court of Justice of the State of Pará. The analysis of this corpus was thought from the Discourse of Bakhtin, where it was possible to identify the senses and meanings that constituted the case records based on the Penal Code of 1890.